Implementasi Model Pembelajaran Problem Based Learning dalam Pembelajaran PPKn - Sunarto Sunarto; Hadi Cahyono; Ratih Yana Lestiana; Deaningm Maharani (Proceedings Series of Educational Studies, 2023)
This article aims to analyze how the implementation of Pancasila and Citizenship Education (Civics) learning for class X students at SMAN 3 Ponorogo through a problem based learning model. The method used was qualitative with informants namely teachers and students at SMAN 3 Ponorogo. Data collection methods use observation, interviews and documentation. The results obtained are that it can be seen that the implementation of problem based learning in class The aim of the problem based learning model is to change students' way of thinking to be more critical and increase their creativity in thinking to face, formulate and solve existing problems. The conclusion of this research is that the implementation of the problem based learning model in class X in Civics subjects is good because it has been able to make class.